2018
DOI: 10.1051/0004-6361/201833699
|View full text |Cite
|
Sign up to set email alerts
|

Fraction of bolometric luminosity absorbed by dust in DustPedia galaxies

Abstract: Aims. We study the fraction of stellar radiation absorbed by dust, f abs , in 814 galaxies of different morphological types. The targets constitute the vast majority (93%) of the DustPedia sample, including almost all large (optical diameter larger than 1 ′ ), nearby (v ≤ 3000 km s −1 ) galaxies observed with the Herschel Space Observatory. Methods. For each object, we model the spectral energy distribution from the ultraviolet to the sub-millimetre using the dedicated, aperture-matched DustPedia photometry an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(113 citation statements)
references
References 111 publications
10
100
0
3
Order By: Relevance
“…In comparison, a slight offset is seen for the Ref-100 sample, which is expected considering the Recal-25 run has a higher resolution and better sampled disks (Trayford et al 2017). For a galaxy property that depends on the geometry of a galaxy, such as f abs (Viaene et al 2016;Bianchi et al 2018), a sample with more realistic spiral galaxies will reach a better agreement with observations. Based on Fig.…”
Section: The Galaxy Populationmentioning
confidence: 80%
See 3 more Smart Citations
“…In comparison, a slight offset is seen for the Ref-100 sample, which is expected considering the Recal-25 run has a higher resolution and better sampled disks (Trayford et al 2017). For a galaxy property that depends on the geometry of a galaxy, such as f abs (Viaene et al 2016;Bianchi et al 2018), a sample with more realistic spiral galaxies will reach a better agreement with observations. Based on Fig.…”
Section: The Galaxy Populationmentioning
confidence: 80%
“…This ratio contains information on how optically thick a galaxy is, which further depends on the amount, composition, and geometry of dust in a galaxy. Previously, studies reported the average value of f abs to be 0.25 ± 0.05 with the highest value for late-type galaxies (Davies et al 2012;Viaene et al 2016;Bianchi et al 2018, and references therein).…”
Section: 2mentioning
confidence: 92%
See 2 more Smart Citations
“…7 also shows the intrinsic stellar SED of M33 (as it would be observed in the absence of dust), with the difference between the apparent (black) and intrinsic (purple) model SED representing the absorption by dust. We have calculated that 35±3% of the stellar light is absorbed by dust and re-emitted in the far-infrared, which is a typical value for late-type spiral galaxies Viaene et al 2016;Bianchi et al 2018). Another aspect of interest shown by Fig.…”
Section: The Global Sed Of M33mentioning
confidence: 96%